Klasifikasi Risiko Hipertensi Menggunakan Metode Neighbor Weighted K-Nearest Neighbor (NWKNN) - Bayu Laksana Yudha; Lailil Muflikhah; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Hypertension or called high blood pressure caused high risk of death in Indonesia. This could trigger sustainable effect to other diseases such as heart attack and kidney failure. According to WHO, as many as 30% of Indonesians are sufferers hypertension, Indonesian Hypertension Doctor Association also said that 76% of cases of hypertension can not diagnosed earlier and therefore hypertension is called a silent killer. The way to handling hypertension earlier is by early detection of hypertension in form of Early Alertness System (SKD). In this research will classified risk of hypertension based on medical record using Neighbor Weigted K-Nearest Neighbor (NWKNN) classification method. This method is the development of the KNN method. In NWKNN there is a weighting process in each class of hypertension risk. In this study, the classification of hypertension into 4 risks that is Normal, Pre Hypertension, Stage 1 and Stage 2. The results of this research shows that the NWKNN method is able to classify the hypertension risk well when tested on 100 training data, 25 testing data, K score=10, and E score=4 with accuracy result that reached 88%.